Comparison of Three Different Doses of Esmolol to Attenuate Hemodynamic Stress Response During Laryngoscopy and Endotracheal Intubation - Sharma, Mahesh; Sapkota, Suraksha; Sharma, Sagun; Shakya, Shailendra (Journal of Nepalgunj Medical College, 2024)
Introduction: The hemodynamic stress can result from laryngoscopy and endotracheal intubation due to sympathoadrenal stimulation. Esmolol administered intravenously reduces the hemodynamic stress response. The lowest effective dose of esmolol for this purpose is still in debate, hence we chose to study three different doses. Aims: To evaluate various doses of esmolol administered intravenously in managing hemodynamic stress response in patients undergoing laryngoscopy and endotracheal intubation. Methods: This prospective and cross-sectional analytical study was conducted among 66 patients, administered 0.5 (Group A), 1 (Group B) and 1.5 mg/kg (Group C) doses of esmolol to 22 patients in each group undergoing laryngoscopy and endotracheal intubation, considering all inclusion and exclusion criteria. Parameters like heart rate, arterial blood pressure were all monitored before premdication, after premdication, before intubation, after intubation, till 7 minutes at different time intervals following laryngoscopy and intubation. Results: The heart rate data for Groups A, B, and C shows significant differences at various stages. For example, post succynylcholine Group data also showed significant differences, particularly at 3 and 4 minutes post-intubation (p<0.001). Mean arterial pressure (MAP) measurements further demonstrate significant differences at multiple stages (e.g., post-intubation MAP: Group A 115.5±8, Group B 108.2±7.2, Group C 109.2±8.9, p<0.001). Conclusion: The study has shown that it is better to choose 1.5 mg/kg to manage hemodynamic stress response during laryngoscopy and endotracheal intubation.